Muroqobah Dalam Fathul Arifin - Hasan, Muhammad Syahrul; Windianti, Fitri; Febriani, Sari (The International Journal of Pegon : Islam Nusantara civilization, 2024)
This study highlights the gap in understanding the concept of muroqobah in "Fathul Arifin" by Sheikh Ahmad Khatib Sambas, as well as its limitations in application to the spiritual life of Muslims in the modern era. Its aim is to address this gap by gaining a deeper understanding of the concept and exploring its potential application in the context of contemporary spiritual life. The research methodology employs a qualitative approach with a case study design, focusing on the interpretation and implementation of the "Muroqobah" concept. Data collection techniques include text analysis, interpretation of meaning, and literature review, with primary data sourced from the digitization of the Fathul 'Arifin manuscript and secondary data from various manuscript catalogs. The analysis results indicate that "Fathul Arifin" serves as a significant guide for practitioners of the Qadariyyah wa Naqsabandiyyah order, facilitating profound reflection on the integration of spirituality into daily life. The concept of muroqobah is not only relevant religiously but also prompts contemplation on responsibility and meaning in life. Thus, the study concludes that the concept of muroqobah holds great potential for strengthening the spirituality of Muslims in the modern era, offering valuable guidance for practitioners of the order and individuals seeking depth in their religious experience. This abstract objectively reflects the content and main objectives of the study, avoiding exaggeration of conclusions or presenting unsupported findings from the main text. Penelitian ini menyoroti kesenjangan dalam pemahaman tentang konsep muroqobah dalam "Fathul Arifin" karya Syeikh Ahmad Khatib Sambas, serta keterbatasan aplikasinya dalam kehidupan spiritual umat Muslim pada zaman modern. Tujuannya adalah untuk mengisi kesenjangan ini dengan memahami secara lebih mendalam konsep muroqobah dan mengeksplorasi potensi aplikasinya dalam konteks kehidupan spiritual saat ini. Metode penelitian ini menggunakan pendekatan kualitatif dengan studi kasus sebagai rancangan utama, dengan fokus pada interpretasi dan implementasi konsep "Muroqobah". Teknik pengumpulan data meliputi analisis teks, penafsiran makna, dan studi literatur, dengan data primer dari digitalisasi Naskah Fathul 'Arifin dan data sekunder dari berbagai katalog naskah. Hasil analisis menunjukkan bahwa karya "Fathul Arifin" adalah panduan penting bagi praktisi tarekat Qadariyyah wa Naqsabandiyyah, membuka pintu bagi refleksi mendalam tentang integrasi spiritualitas dalam kehidupan sehari-hari. Konsep muroqobah tidak hanya relevan secara keagamaan, tetapi juga mengundang untuk merenungkan tanggung jawab dan makna dalam kehidupan. Dengan demikian, penelitian ini menyimpulkan bahwa konsep muroqobah memiliki potensi besar untuk memperkuat spiritualitas umat Muslim pada era modern, memberikan panduan berharga bagi praktisi tarekat dan individu yang mencari kedalaman dalam pengalaman keagamaan mereka. Abstrak ini mencerminkan secara objektif konten dan tujuan utama penelitian, tanpa memperbesar kesimpulan atau menyajikan hasil yang tidak terbukti dalam teks utama.